Interrelationships between negative mood and clinical constructs: a motivational systems approach - Britton, Gary I.; Davey, Graham C. L. (Frontiers in Psychology, 2014)
A series of three experiments was designed to test predictions from a motivational systems approach to understanding the role of clinical constructs in anxiety-based problems. Negative mood, inflated responsibility and intolerance of uncertainty (IU) were separately manipulated within analogue samples to examine their effect on the other two factors. In the first experiment (n = 59) the negative mood group scored significantly higher in terms of inflated responsibility than the positive mood group. In the second experiment (n = 63) the high responsibility group scored significantly higher in terms of both negative mood and IU than the low responsibility group. In the third experiment (n = 61) the high IU group scored significantly higher in terms of negative mood than the low IU group. Tests of indirect effects revealed an indirect effect of IU on inflated responsibility through negative mood and an indirect effect of negative mood on IU through inflated responsibility, suggesting all three constructs are casually interrelated. The findings are consistent with contemporary transdiagnostic views of clinical constructs, and support a view of anxiety that is underpinned by a coordinated and interdependent motivational system evolved to manage threat.